Pengaruh Tingkat Literasi Keuangan Syariah terhadap Kinerja Karyawan Bank Sumsel Babel KC Syariah Palembang - Pini Julistiana, Pini Julistiana; Isni Andriana, Isni Andriana; Shelfi Malinda, Shelfi Malinda (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study was to determine the effect of the level of Islamic financial literacy on employee performance with the research object being employees of the Sumsel Babel Bank, Sharia Branch Office Palembang. This study uses a saturated sample technique. Questionnaires were distributed to 41 employees of Sumsel Babel Bank, Sharia Branch Office Palembang. Data were analyzed using SPSS. The results of the study show that Islamic financial literacy has no significant effect on employee performance.